Función de la música y la indumentaria como signos de la identidad andina en Diamantes y pedernales - Alcántara Silva, Ynés V. (2019)
The cultural manifestations of the Andean world have an important expression in the narrative of José María Arguedas. In the novel Diamantes y pedernales, the music acts as a unifying and revitalizing factor of the Andean culture, for which it is articulated with the principles of its cosmovision. From this point of view, the music is closely related to the different beings that constitute the Andean universe. Thus, the characters, musical instruments, rituals and the social and cultural practices share an interrelation and inter-influence. On the other hand, the clothing, made up of a series of garments or outfits typical of the indigenous community, distinguishes and identifies the characters in the novel and is associated with certain meanings. Both the music with its function ofrevitalization of the Andean world and the clothing of the characters contribute to affirm the identity of the indigenous community in the world represented in Diamantes y pedernales.